English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2 answers

y = 3x^2 - 7x - 8

Goal: to get this into y = a(x - h)^2 + k form;
Your axis of symmetry is going to be x = h.

You must complete the square to accomplish this.

y = 3(x^2 - (7/3)x) - 8

y = 3(x^2 - (7/3)x + 49/36) - 8 - 3(49/36)

y = 3(x - (7/6))^2 - 8 - 49/12

Since it's the number in brackets we care about, we need not merge the numbers outside of the brackets into a single fraction.

Our axis of symmetry is x = 7/6.

2007-03-12 19:53:17 · answer #1 · answered by Puggy 7 · 0 0

y = 3.[x² - (7/3 ).x - 8/3]
y = 3.[ (x² - (7/3).x + 49/36) - 49/36 - 8/ 3]
y = 3.[(x - 7/6)² - 49/36 - 8/3]
Axis of symmetry is x = 7/6

2007-03-12 22:05:19 · answer #2 · answered by Como 7 · 0 0

fedest.com, questions and answers